Crystalline Subtype of Pre-Descemetic Corneal Dystrophy - Rosa Dolz-Marco; Roberto Gallego-Pinazo; María Dolores Pinazo-Durán2; Manuel Díaz-Llopis (Journal of Ophthalmic & Vision Research, 2014)
Purpose: To report corneal findings in a familial case of the crystalline subtype of pre- Descemetic corneal dystrophy. Case Report: A 19-year-old girl and her 44-year-old mother were found to have asymptomatic, bilateral, punctiform and multi-colored crystalline opacities across the whole posterior layer of the corneas. Endothelial specular microscopy revealed the presence of white round flecks located at different levels anterior to the endothelium. No systemic abnormalities or medications could be related to account for these findings. Conclusion: To the best of our knowledge, this is the third familial report of this rare corneal disorder. Differential diagnosis may include Schnyder corneal dystrophy, cystinosis, Bietti΄s dystrophy and monoclonal gammopathy.